Serotonin Regulates Calcium Homeostasis in Lactation by Epigenetic Activation of Hedgehog Signaling - Laporta, Jimena (Endocrine Society, 2014)
Calcium homeostasis during lactation is critical for maternal and neonatal health. We previously showed that nonneuronal/peripheral serotonin [5-hydroxytryptamine (5-HT)] causes the lactating mammary gland to synthesize and secrete PTHrP in an acute fashion. Here, using a mouse model, we found that genetic inactivation of tryptophan hydroxylase 1 (Tph1), which catalyzes the rate-limiting step in peripheral 5-HT synthesis, reduced circulating and mammary PTHrP expression, osteoclast activity, and maternal circulating calcium concentrations during the transition from pregnancy to lactation. Tph1 inactivation also reduced sonic hedgehog signaling in the mammary gland during lactation. Each of these deficiencies was rescued by daily injections of 5-hydroxy-L-tryptophan (an immediate precursor of 5-HT) to Tph1-deficient dams. We used immortalized mouse embryonic fibroblasts to demonstrate that 5-HT induces PTHrP through a sonic hedgehog-dependent signal transduction mechanism. We also found that 5-HT altered DNA methylation of the Shh gene locus, leading to transcriptional initiation at an alternate start site and formation of a variant transcript in mouse embryonic fibroblasts in vitro and in mammary tissue in vivo. These results support a new paradigm of 5-HT-mediated Shh regulation involving DNA methylation remodeling and promoter switching. In addition to having immediate implications for lactation biology, identification and characterization of a novel functional regulatory relationship between nonneuronal 5-HT, hedgehog signaling, and PTHrP offers new avenues for the study of these important factors in development and disease.